2011
DOI: 10.1042/bj20110750
|View full text |Cite
|
Sign up to set email alerts
|

Aβ42 oligomers, but not fibrils, simultaneously bind to and cause damage to ganglioside-containing lipid membranes

Abstract: Aβ (amyloid-β peptide) assembles to form amyloid fibres that accumulate in senile plaques associated with AD (Alzheimer's disease). The major constituent, a 42-residue Aβ, has the propensity to assemble and form soluble and potentially cytotoxic oligomers, as well as ordered stable amyloid fibres. It is widely believed that the cytotoxicity is a result of the formation of transient soluble oligomers. This observed toxicity may be associated with the ability of oligomers to associate with and cause permeation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 44 publications
9
89
0
Order By: Relevance
“…This observed toxicity may be associated with the ability of oligomers to bind with and cause permeation of cell lipid membrane. The binding may partly be mediated by the GM1 (monosialo) ganglioside receptors expressed in the outer leaflet of vertebrate membrane [30]. Additionally, bar graph of tail lengths of HSA confirms the above results as deduced from images (Fig.…”
Section: Q5supporting
confidence: 87%
“…This observed toxicity may be associated with the ability of oligomers to bind with and cause permeation of cell lipid membrane. The binding may partly be mediated by the GM1 (monosialo) ganglioside receptors expressed in the outer leaflet of vertebrate membrane [30]. Additionally, bar graph of tail lengths of HSA confirms the above results as deduced from images (Fig.…”
Section: Q5supporting
confidence: 87%
“…These results are in agreement with in vivo studies where aggregation seems to be increased at the level of membrane rafts (21,24,25). However, the binding of preformed Aβ oligomers and amylin aggregates to synthetic lipid vesicles, an event that induces membrane permeabilization, appears to be driven by GM1 (21,26). It has also been demonstrated that exogenous Aβ1-42 oligomers applied to cultured neurons tend to accumulate on the membrane at the level of rafts enriched in GM1 (25).…”
Section: Gm1 In Alzheimer's Disease and Other Amyloid Pathologiessupporting
confidence: 81%
“…Extraction for the analysis of disease-associated changes (11) In vitro Biological membrane model (3,4,20,22,23,26,32) In vitro SIMS of individual isotope-labeled lipid components (3) In vitro Column of immobilized beads functionalized with a target protein and mass spectrometry (6) In vitro Single fluorescent molecule imaging and tracking (9,28,29) In vivo Molecular dynamics (5,35,36) In silico…”
Section: Ganglioside Investigation Methods Applicationmentioning
confidence: 99%
“…In comparison, oligomeric and fibrillar self-assembled structures of full-length Aβs were found to form on different supported membranes. 5357 …”
Section: Resultsmentioning
confidence: 99%